Perioperative Pain and Addiction Interdisciplinary Network (PAIN) clinical practice advisory for perioperative management of buprenorphine: results of a modified Delphi process. (August 2019) - Goel, Akash; Azargive, Saam; Weissman, Joel S.; Shanthanna, Harsha; Hanlon, John G.; Samman, Bana; Dominicis, Mary; Ladha, Karim S.; Lamba, Wiplove; Duggan, Scott; Di Renna, Tania; Peng, Philip; et al.
Summary: Until recently, the belief that adequate pain management was not achievable while patients remained on buprenorphine was the impetus for the perioperative discontinuation of buprenorphine. We aimed to use an expert consensus Delphi-based survey technique to 1) specify the need for perioperative guidelines in this context and 2) offer a set of recommendations for the perioperative management of these patients. The major recommendation of this practice advisory is to continue buprenorphine therapy in the perioperative period. It is rarely appropriate to reduce the buprenorphine dose irrespective of indication or formulation. If analgesia is inadequate after optimisation of adjunct analgesic therapies, we recommend initiating a full mu agonist while continuing buprenorphine at some dose. The panel believes that before operation, physicians must distinguish between buprenorphine use for chronic pain (weaning/conversion from long-term high-dose opioids) and opioid use disorder (OUD) as the primary indication for buprenorphine therapy. Patients should ideally be discharged on buprenorphine, although not necessarily at their preoperative dose. Depending on analgesic requirements, they may be discharged on a full mu agonist. Overall, long-term buprenorphine treatment retention and harm reduction must be considered during the perioperative period when OUD is a primary diagnosis. The authors recognise that inter-patient variability will require some individualisation of clinical practice advisories. Clinical practice advisories are largely based on lower classes of evidence (level 4, level 5). Further research is required in order to implement meaningful changes in practitioner behaviour for this patient group.